2020
DOI: 10.1186/s12879-020-05090-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment in treatment-experienced adults living with HIV attending primary care clinics in Zimbabwe

Abstract: Background: HIV affects the central nervous system resulting in HIV associated neurocognitive impairment (NCI) in approximately 50% of people living with HIV. It typically affects memory, learning, working memory, fine motor skills, speed of information processing, verbal fluency and executive functioning cognitive domains. NCI can affect adherence to antiretroviral therapy (ART), employability, driving ability and activities of daily living. NCI is not routinely screened for in Zimbabwe, and the burden is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The predominant prevalence of the moderate forms of neurocognitive disorders could explain the clinical features, characterized mainly by the impairment in the domains attention and memory. A similar observation was found in Zimbabwe [16]. The disorders in attention, concentration and memory, meaning a subcortical dysfunction, are known to be the initial symptoms at the occurring of neurocognitive disorders.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The predominant prevalence of the moderate forms of neurocognitive disorders could explain the clinical features, characterized mainly by the impairment in the domains attention and memory. A similar observation was found in Zimbabwe [16]. The disorders in attention, concentration and memory, meaning a subcortical dysfunction, are known to be the initial symptoms at the occurring of neurocognitive disorders.…”
Section: Discussionsupporting
confidence: 76%
“…Other factors such as the gender, the nadir of CD4, the coinfection HIV-Hepatitis C are reported as risk factors of neurocognitive disorders, but were not found in our study. On the other hand, NSC3 was found to be a factor associated with neurocognitive disorders in our study, everything not having been reported previously, for example in Kenya and Zimbabwe [10,16]. Further analysis could be helpful to explain this result.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The removal of duplicates and application of the inclusion and exclusion criteria at the title and abstract screening stage yielded 128 articles for full-text screening. Of these, 40 studies (see Table 1) met the requirements for quantitative analyses, while seven studies (Do et al, 2018;Ene et al, 2014;Kore et al, 2015;Nyamayaro et al, 2020;Salahuddin et al, 2020;Tsegaw et al, 2017;Yuan et al, 2013) were not included in the meta-analyses due to insufficient data to compute effect sizes or not containing any data to be used for meta-analyses. Of the 40 studies, 24 studies were cross-sectional, 13 studies were longitudinal, and three studies were randomized controlled trials [see Table 1].…”
Section: Search Resultsmentioning
confidence: 99%
“… 40 This suggests that neurocognitive deficits, including memory, limit a person’s ability to reject social stereotypes. 39 , 41 In addition, people with HIV are vulnerable to HIV self-stigma, which translates into a greater level of agreement with negative beliefs associated with their identity. 39 However, studies analysing the relationship between cognitive abilities and HIV self-stigma in this group are scarce.…”
Section: Introductionmentioning
confidence: 99%